Complexity and Genetic Variability of Heat-Shock Protein Expression in Isolated Maize Microspores. - Magnard, J. L. (1996)
The expression of heat-shock proteins (HSPs) in isolated maize (Zea mays L.) microspores has been investigated using high-resolution two-dimensional electrophoresis coupled to immunodetection and fluorography of in vivo synthesized proteins. To this end, homogeneous and viable populations of microspores have been purified in sufficient amounts for molecular analysis from plants grown in controlled conditions. Appropriate conditions for thermal stress application have been defined. The analysis revealed that isolated microspores from maize display a classical heat-shock response characterized by the repression of the normal protein synthesis and the expression of a set of HSPs. A high complexity of the response was demonstrated, with numerous different HSPs being resolved in each known major HSP molecular weight class. However, the extent of this heat-shock response is limited in that some of these HSPs do not accumulate at high levels following temperature elevation. Comparative analysis of the heat-shock responses of microspores isolated from five genotypes demonstrated high levels of genetic variability. Furthermore, many HSPs were detected in microspores at control temperature, indicating a possible involvement of these proteins in pollen development at stages close to first pollen mitosis.